2007
DOI: 10.1161/atvbaha.106.138990
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of a Proinflammatory Phenotype in Monocyte-Derived Macrophages From Subjects With Low Plasma HDL-Cholesterol

Abstract: Objective-Reduced plasma concentrations of high-density lipoprotein-cholesterol (HDL-C) are a significant risk factor for cardiovascular disease. Mechanisms that regulate HDL-C concentrations represent an important area of investigation. Methods and Results-Comparative transcriptome analyses of monocyte-derived macrophages (MDM) from a large population of low HDL-C subjects and age-and sex-matched controls revealed a cluster of inflammatory genes highly expressed in low HDL-C subjects. The expression levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Although about 30% of low-HDL subjects exhibited cellular cholesterol efflux defects, the majority of these subjects did not harbor functional mutations in ABCA1. A recent observation that the activated proinflammatory state of the monocytes and macrophages in low-HDL subjects may contribute to the pathophysiological consequences of low HDL prompted us to test for this in our sample (23). In the present study, quantitative RT-PCR analysis for relative Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although about 30% of low-HDL subjects exhibited cellular cholesterol efflux defects, the majority of these subjects did not harbor functional mutations in ABCA1. A recent observation that the activated proinflammatory state of the monocytes and macrophages in low-HDL subjects may contribute to the pathophysiological consequences of low HDL prompted us to test for this in our sample (23). In the present study, quantitative RT-PCR analysis for relative Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Relative mRNA expression levels of ABCA1 and ABCG1 were recorded to assess the possible contributions of the two efflux pathways. Because a previous study (23) reported a proinflammatory state in monocytes and monocyte-derived macrophages from low HDL-C subjects, we also measured mRNA expression of selected inflammatory genes in monocytes isolated from the study subjects.…”
mentioning
confidence: 99%
“…In addition, glycosylation of apoA1, which primarily acts via ABCA1, has been shown to suppress its ability to remove cholesterol from cells (74). HDL also has anti-inflammatory and anti-oxidant properties in cells of the vessel wall (75; 76) Monocyte-derived macrophages isolated from subjects with low HDL cholesterol manifest a pro-inflammatory phenotype (77).…”
Section: Hdl In Diabetesmentioning
confidence: 99%
“…34 Moreover, monocyte-derived macrophages isolated from individuals with low HDL cholesterol concentrations manifest a proinflammatory phenotype. 35 Therefore, mean and maximum TBR may be associated with low HDL cholesterol and increased small, dense LDL particles rather than circulating LDL cholesterol level. The results of this study also showed that hyperglycemia-related variables, such as the fasting plasma glucose and HbA 1c , were significantly associated with the vascular inflammation measured by FDG-PET.…”
Section: Figurementioning
confidence: 99%